2010
DOI: 10.1534/genetics.110.118695
|View full text |Cite
|
Sign up to set email alerts
|

Bap170, a Subunit of the Drosophila PBAP Chromatin Remodeling Complex, Negatively Regulates the EGFR Signaling

Abstract: BAP and PBAP constitute the two different forms of the Drosophila melanogaster Brahma chromatin remodelers. A common multisubunit core, containing the Brahma ATPase, can associate either with Osa to form the BAP complex or with Bap170, Bap180, and Sayp to constitute the PBAP complex. Although required for many biological processes, recent genetic analyses revealed that one role of the BAP complex during Drosophila wing development is the proper regulation of EGFR target genes. Here, we show that Bap170, a dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…For example, PBAP but not BAP is required for germinal stem cell maintenance (He et al 2014). Moreover, BAP and PBAP have opposing roles in Egfr expression in wing development: whereas BAP positively regulates Egfr expression (Molnar et al 2006; Terriente-Felix and de Celis 2009), PBAP instead negatively regulates Egfr (Rendina et al 2010). Together, these observations suggest that mutations in different subunits or complexes may result in distinct or even opposing changes to the genomic landscape, a fact that complicates straightforward predictions of their effects.…”
Section: Bap and Pbap In Drosophila Melanogastermentioning
confidence: 99%
“…For example, PBAP but not BAP is required for germinal stem cell maintenance (He et al 2014). Moreover, BAP and PBAP have opposing roles in Egfr expression in wing development: whereas BAP positively regulates Egfr expression (Molnar et al 2006; Terriente-Felix and de Celis 2009), PBAP instead negatively regulates Egfr (Rendina et al 2010). Together, these observations suggest that mutations in different subunits or complexes may result in distinct or even opposing changes to the genomic landscape, a fact that complicates straightforward predictions of their effects.…”
Section: Bap and Pbap In Drosophila Melanogastermentioning
confidence: 99%
“…This construct was used to obtain 20 independent transgenic lines, which were examined for the genomic insertion sites and orientations of the constructs. Driver transgenes for expression of LexA:SAYP or LexA:BAP170 were prepared using either the ubiquitous alpha-tubulin promoter (Ptub) or the less potent BAP170 promoter (PBAP170) to simulate nearly physiological levels of both subunits ( Fig 1B) [16]. As a control, a transgene was constructed to ensure ubiquitous expression of the LexA repressor under the Ptub promoter ( Fig 1B).…”
Section: In Vivo Targeting Of Sayp or Bap170 To A Minimal Promoter Mementioning
confidence: 99%
“…A common core complex includes Brahma (BRM, SMARCA2/4 in human and STH1/SNF2 in yeast), Moira (MOR, SMARCC1/2 in human and SWI3/RSC8 in yeast), and Snr1 (SMARCB1 in human and SNF5/ SFH1 in yeast) and can associate with the distinctive subunit OSA (ARID1A/B in human and SWI1 in yeast) to form the BAP complex or, alternatively, with Polybromo (PB, PBRM1 in human and RSC1/2/4 in yeast), BAP170 (ARID2 in human and RSC9 in yeast), and SAYP (PHF10 in human, no homolog in yeast) to produce the PBAP form [11,12]. Analysis of mutations affecting the signature subunits has demonstrated that BAP and PBAP execute distinct and partly antagonistic functions in transcription control and development with BAP being mainly involved in cell cycle regulation and PBAP, in signal transduction cascades and differentiation [12][13][14][15][16][17]. Interestingly, the PBAP subunits have a hierarchical role in the stability of the complex.…”
Section: Introductionmentioning
confidence: 99%
“…Several TrxG complexes are involved in control of vein vs intervein fate. Indeed, BAP and PBAP chromatin remodeling complexes participate in differential regulation of rho expression [20], [24], [25]. Furthermore, the Chromodomain Helicase DNA-binding protein encoded by the TrxG gene kismet ( kis ) [26], [27] also plays a role in vein development [28].…”
Section: Introductionmentioning
confidence: 99%